The Failure Mechanism of Concrete Gravity Dams considering Different Nonlinear Models under Strong Earthquakes - Chunli Yan; Jin Tu; Deyu Li; Shengshan Guo; Hui Liang (Shock and Vibration, 2021)
The paper focuses on the failure process and mechanism of the concrete gravity dam considering different nonlinear models under strong earthquakes. By taking a typical monolith of a concrete gravity dam as a case study, a comparative analysis of the failure process and mechanism of the dam considering the plastic damage model and the dynamic contact model, respectively, is performed using the seismic overload method. Moreover, the ultimate seismic capacity of the dam is evaluated for both of the nonlinear models. It is found that the ultimate seismic capacity of the dam is slightly different, but the failure process has significant distinctions in each model. And, the damage model is recommended when the conditions permit.